Impact of protein binding on the analytical detectability and anticancer activity of thymoquinone - El-Najjar, Nahed (Springer-Verlag, 2011)
Thymoquinone (TQ), an active component of Nigella sativa L., is known to have anti-cancer and anti-inflammatory effects; however, no studies on its analytical detection in serum and its protein binding have been published. Using high performance liquid chromatography analysis, we show that the average recovery of TQ from serum is 2.5% at 10 μg/ml of TQ and 72% at 100 μg/ml. The low recovery of TQ from serum is due to its extensive binding to plasma proteins, as more than 99% of TQ was bound within 30 min of incubation. The binding of TQ to the major plasma proteins, bovine serum albumin (BSA) and alpha −1 acid glycoprotein (AGP), was studied and found to be 94.5 ± 1.7% for BSA and 99.1 ± 0.1% for AGP. Mass spectrometric analysis revealed that TQ was bound covalently to BSA, specifically on Cyst-34. Using WST-1 proliferation assay, we showed that BSA plays a protective role against TQ-induced cell death; pre-incubation with BSA prevented TQ from exerting its anti-proliferative effects against DLD-1 and HCT-116 human colon cancer cells. On the other hand, binding of TQ to AGP did not alter its anti-proliferative activity against both cell lines. When TQ was pre-incubated with AGP prior to the addition of BSA, the activity of TQ against DLD-1 was maintained, suggesting that AGP prevented the binding of TQ to BSA. This is the first time the covalent binding and inhibitory effect of BSA on TQ is documented. These data offer new grounds for TQ future pharmacokinetic analysis in vivo. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12154-010-0052-4) contains supplementary material, which is available to authorized users.